Genetic structure of populations of Rhizoctonia solani anastomosis group-1 IA from soybean in Brazil - Ciampi, M. B. [UNESP]; Meyer, M. C.; Costa, M. J. N.; Zala, M.; McDonald, B. A.; Ceresini, P. C. [UNESP] (Amer Phytopathological Soc, 2008)
The Basidiomycete fungus Rhizoctonia solani anastomosis group (AG)-1 IA is a major pathogen of soybean in Brazil, where the average yield losses have reached 30 to 60% in some states in Northern Brazil. No information is currently available concerning levels of genetic diversity and population structure for this pathogen in Brazil. A total of 232 isolates of R. solani AG1 IA were collected from five soybean fields in the most important soybean production areas in central-western, northern, and northeastern Brazil. These isolates were genotyped using 10 microsatellite loci. Most of the multilocus genotypes (MLGTs) were site-specific, with few MLGTs shared among populations. Significant population subdivision was evident. High levels of admixture were observed for populations from Mato Grosso and Tocantins. After removing admixed genotypes, three out of five field populations (Maranhao, Mato Grosso, and Tocantins), were in Hardy-Weinberg (HW) equilibrium, consistent with sexual recombination. HW and gametic disequilibrium were found for the remaining soybean-infecting populations. The findings of low genotypic diversity, departures from HW equilibrium, gametic disequilibrium, and high degree of population subdivision in these R. solani AG-1 IA populations from Brazil are consistent with predominantly asexual reproduction, short-distance dispersal of vegetative propagules (mycelium or sclerotia), and limited long-distance dispersal, possibly via contaminated seed. None of the soybean-infecting populations showed a reduction in population size (bottleneck effect). We detected asymmetric historical migration among the soybean-infecting populations, which could explain the observed levels of subdivision.